(untitled) (Theological Kronos, 2019)
The reencounter of the meaning of the biblical text in the midst of the situations that the communities live in the present times is of vital importance for the now Church. A reading of the Bible where people can participate and see their dreams, hopes, fears and pains reflected, is very important for the reconstruction of the texts of the past and the construction of peace in the present, based on reflection of those texts. That is the proposal of a communitarian and contextual reading of the book of Revelation.